2018
DOI: 10.1155/2018/7293861
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3: A New Regulator of Cardiovascular Diseases

Abstract: Cardiovascular diseases (CVDs) are the leading causes of death worldwide, and defects in mitochondrial function contribute largely to the occurrence of CVDs. Recent studies suggest that sirtuin 3 (SIRT3), the mitochondrial NAD+-dependent deacetylase, may regulate mitochondrial function and biosynthetic pathways such as glucose and fatty acid metabolism and the tricarboxylic acid (TCA) cycle, oxidative stress, and apoptosis by reversible protein lysine deacetylation. SIRT3 regulates glucose and lipid metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
113
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 147 publications
3
113
1
Order By: Relevance
“…SIRT3 is one of the sirtuins of NAD‐dependent deacetylases and located in mitochondria . SIRT3 is involved in the processes of energy metabolism and development of diseases including the cancer, cardiovascular, and nervous systems . SIRT3 adjusts several mitochondrial functions, such as managing ROS, ATP production, and cell death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT3 is one of the sirtuins of NAD‐dependent deacetylases and located in mitochondria . SIRT3 is involved in the processes of energy metabolism and development of diseases including the cancer, cardiovascular, and nervous systems . SIRT3 adjusts several mitochondrial functions, such as managing ROS, ATP production, and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…25 SIRT3 is involved in the processes of energy metabolism and development of diseases including the cancer, cardiovascular, and nervous systems. [26][27][28] SIRT3 adjusts several mitochondrial functions, 29,30 such as managing ROS, ATP production, and cell death. In the previous studies, it has been reported that the expression level of SIRT3 suppressed in several malignant tumor, [31][32][33] including prostate, lung, and gastric cancers.…”
mentioning
confidence: 99%
“…All of these are the intermediate products of lipid, glucose, and protein metabolism whereas MnSOD is a potent mitochondrial antioxidant. Other than this, SIRT3 also deacetylates components of electron transport chain complexes like NDUFA9, ATP synthases, succinate dehydrogenase, and flavoprotein [ 1 , 14 , 15 , 21 , 22 ]. SIRT3 also enhances the activities of the adenosine monophosphate-activated protein kinase (AMPK) and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1 α ) and increases the daf-16 homolog FOXO3a-dependent gene expressions.…”
Section: Introductionmentioning
confidence: 99%
“…The full-length SIRT3 protein is 44 kDa and contains 399 residues with an N-terminal mitochondrial targeting sequence and is enzymatically inactive, which is processed to produce an active 28 kDa polypeptide by cleaving the N-terminal 101 residue upon import into the mitochondrial matrix [ 24 28 ]. SIRT3 plays a major role in the mitochondrial energy production and the metabolic homeostasis [ 22 ]. NAD has a critical role in ATP generation in the mitochondria, and it is an electron carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress (OS) is produced by the imbalance between free radical production and antioxidant defence. Oxidative stress has both positive and negative effects on the body, however, they are effective in several host defence mechanisms like hydrolysis of pathogens and denaturation of antigens that invading into the body and is considered to be harmful when the OS damages the body cells and tissues by peroxidation of lipid membrane, oxidation of protein or DNA and disruption of cytokines, development of various diseases, cell injury and apoptosis 2,3 .…”
Section: Introductionmentioning
confidence: 99%